إيضاح ممن تسمى باسم محمد الكريم في الجاهلية تأليف أبي خليل بن أبي الإمداد برهان الدين اللَّقَّاني (ت1104ه) - عبد الله كامران سعد الله (Al-Adab Journal, 2018)
This research deals with a number of people named as Mohammed before Islam, and adjusts their pronunciation, genealogy, etc. It demonstrates the number of the people named by that name before Islam; they were under twenty. It also demonstrates the number of those known by that name according to every scholar and the dispute among themselves about their number, and the reason of being named Mohammed. The author has divided his book into an introduction, the reason for writing the book, an alert, an important usefulness, and sequel I and II. He entitled his book (Demonstration of those named Mohammad before Islam). I have divided my research into an introduction, twelve chapters, the investigated text and a conclusion. The first chapter: the biography of Khalil Al-Laqqany and the mentioning of his books by historians. The second chapter: his name, nickname, surname, doctrine and descend. The third chapter: his birth, scholars’ praise to him, his trips, and his death. Chapter four: his family and his works according to the alphabet. The fifth chapter: his teachers. The sixth chapter: his disciples. Chapter seven: definition of the content of the book and its approach. Chapter eight: resources in his book. Chapter nine: drawbacks and illusions on the book and its importance and his views and his choices in the book. Chapter ten: the title of the book documented and attributed to the author. Chapter eleven: description of the hand-written copies relied on in the investigation. Chapter twelve: Work approach in investigating this book. Chapter thirteen: symbols and terms that I have used in the investigation of the book.